The Phillips curve in the euro area: New evidence using country-level data - Susanne Wellmann (University of Tübingen, Faculty of Economics and Social Sciences, 2023)
We study whether the trade-off between inflation and unemployment still exists in the euro area (EA). Using country-level data for member states of the EA, we estimate a refined specification of the Phillips curve in the spirit of Hazell et al. (2022) deploying a non-tradable price index to measure inflation. We find that the slope of the Phillips curve is small and hence the Phillips curve is flat in the EA, similarly to the US. Moreover, reference estimates based on aggregate data overstate the steepness of the Phillips curve considerably. Our findings imply that the insensitivity of inflation with respect to unemployment over the last decade is a result of firmly anchored inflation expectations.
urn:nbn:de:bsz:21-dspace-1383603
Keywords: E31; D84; F45; 330; Inflation; Phillips curve; Expectations; Euro Area